2005
DOI: 10.1002/cncr.21013
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and time course changes in regional distribution of fat and lean tissue in unselected cancer patients on palliative care—Correlations with food intake, metabolism, exercise capacity, and hormones

Abstract: BACKGROUNDSeveral investigations that yielded different results in terms of net changes in body composition of weight‐losing cancer patients have been reported that employed a variety of methods based on fundamentally different technology. Most of those reports were cross‐sectional, whereas to the authors' knowledge there is sparse information available on longitudinal follow‐up measurements in relation to other independent methods for the assessment of metabolism and performance.METHODSFor the current report,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
205
1
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(229 citation statements)
references
References 49 publications
15
205
1
8
Order By: Relevance
“…Cancer cachexia induces wasting of fat mass that accounts for a large part of the dramatic weight loss observed both in humans (Fouladiun et al 2005, Agustsson et al 2007, Dahlman et al 2010) and in animals (Machado et al 2004, Bing et al 2006, Asp et al 2010, and lipid metabolism is markedly altered (Seelaender et al 1996, Tisdale 2009, Arner 2011. Walker 256-induced cachexia was efficient at eliciting loss of body weight in terms of both absolute and relative weight (percentage of total body mass) of the fat depots, with consequent abnormalities in plasma biochemical profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer cachexia induces wasting of fat mass that accounts for a large part of the dramatic weight loss observed both in humans (Fouladiun et al 2005, Agustsson et al 2007, Dahlman et al 2010) and in animals (Machado et al 2004, Bing et al 2006, Asp et al 2010, and lipid metabolism is markedly altered (Seelaender et al 1996, Tisdale 2009, Arner 2011. Walker 256-induced cachexia was efficient at eliciting loss of body weight in terms of both absolute and relative weight (percentage of total body mass) of the fat depots, with consequent abnormalities in plasma biochemical profile.…”
Section: Discussionmentioning
confidence: 99%
“…During the development of cancer cachexia, a well-characterised loss of both adipose tissue and skeletal muscle occurs (Dahlman et al 2010, Arner 2011. It has been proposed that the former often precedes and is more rapid than the latter (Fouladiun et al 2005). Several factors culminate in loss of adipose tissue, such as 1) increased lipid mobilisation due to enhanced adipocyte lipolysis (Agustsson et al 2007, Ryden et al 2008, Arner 2011, 2) reduced lipogenesis due to decreased lipoprotein lipase activity (Tisdale 2009) and 3) impairment of fat cell turnover, which results in a disruption in the formation and development of adipose tissue (Arner & Spalding 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that in cancer cachexia, loss of WAT mass is related to anorexia and to a decrease in food intake, whereas skeletal muscle loss is more related with increased proteolysis (Fouladiun et al 2005). This does not seem to be the case in adjuvant arthritis, since pair-fed rats, although they have lower body weight than control ad libitum fed rats, have a relative WAT weight similar to them.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated patients with gastrointestinal cancer who had no evidence of gastrointestinal obstruction, and were either weight stable or with evident cachexia. We focused on adipose tissue as preferential wasting of this tissue is involved in the early stages of disease (Fouladiun et al, 2005). Our primary hypothesis was that changes in pathways involved in the regulation of energy metabolism would accompany loss of adipose tissue in cachexia.…”
mentioning
confidence: 99%